“ANUGRAH” DAYA TARIK WISATA LUMBA-LUMBA BERBASIS TRI HITA KARANA PANTAI LOVINA BULELENG – BALI - Ketut Sumadi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The benefits of tourism development are greatly felt in improving the welfare of the resi- dents of the Traditional Village who manage the tourist attraction of Dolphins in the Lovina Beach area. For example, the residents of Kalibukbuk Traditional Village acknowledge that this great benefit is a gift (blessing) from Ida Sang Hyang Widhi / God Almighty. The management of the tourist attraction of Dolphins in the perspective of the Social Exchange theory which empha- sizes that social behavior involves psychological problems where people engage in social be- havior to get rewards that are intrinsic or economic, so that the development of tourism in the Traditional Village in the Lovina Beach Tourism Area, Singaraja - Bali contains the meaning of welfare for customary village manners according to the concept of Tri Hita Karana and the goal of Hinduism, namely moksartham jagadhita. This is also in accordance with the objectives of developing cultural tourism, namely providing benefits to local communities, preserving cul- ture, respecting religious norms and maintaining local wisdom traditions. The Kalibukbuk Tra- ditional Village community, especially fishermen and tourism managers in the Lovina Beach area have realized that the management of the tourist attraction of Dolphins in the Tri Hita Karana based Lovina Beach Tourism Area has provided economic and social religious benefits.